2018
DOI: 10.1109/lra.2018.2803204
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Synthetic Fiber Ropes and Frequency Response of Long-Distance Cable–Pulley System

Abstract: In recent years, synthetic fiber ropes have attracted much attention because of their potential to increase the load capacity, reduce the size, and lighten the weight of tendondriven mechanisms. However, the mechanical characteristics of synthetic fiber ropes in a dynamic loading situation remain an open problem because of their visco-elasto-plasticity. This paper focuses on modeling synthetic fiber ropes, and the frequency response of a long-distance cable-pulley system for a tendondriven robot. We show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…On the other hand, the tension increased immediately after the current command value was changed and then decreased gradually. This is considered to result from the viscoelasticity of the synthetic fiber rope, as shown in the literature [22]. The above demonstrates that this method is very effective for mounting press-fit parts on robots made by 3D printers.…”
Section: B Tension Load Testmentioning
confidence: 71%
“…On the other hand, the tension increased immediately after the current command value was changed and then decreased gradually. This is considered to result from the viscoelasticity of the synthetic fiber rope, as shown in the literature [22]. The above demonstrates that this method is very effective for mounting press-fit parts on robots made by 3D printers.…”
Section: B Tension Load Testmentioning
confidence: 71%
“…We selected a 2 mm-diameter Dyneema rope (tensile strength of 4.29 kN, DB-96HSL, Hayami industry) as the JCTs because of these characteristics. We intensively investigated the basic mechanical properties of various types of synthetic fiber ropes in our previous work [15] [16] [17], and found that Dyneema had the highest durability against sharp repetitive bending.…”
Section: Synthetic Fiber Ropementioning
confidence: 99%
“…Thus, if we were to fully exploit these advantages of synthetic fiber ropes, it may be possible to develop a high performance robot, which is not feasible with conventional mechanisms. In our previous works, we investigated modeling of synthetic fiber ropes [3], tensile strength degradation by bending [4], repetitive bending durability [5], and the terminal fixation method [6].…”
Section: Introductionmentioning
confidence: 99%